Indigeneity, citizenship and the state : perspectives from India's Northeast - Kikhi, Kedilezo; Das, Amiya Kumar; Dutta, Piyashi (London : Routledge, 2023)
Whatever be the definition of 'indigenous' vis-a-vis 'indigeneity', and however concensual it might be, both these terms have been inferred, applied and questioned in multifarious ways. The concept indigeneity in Asia has transformed considerably, over a period of time. With the rise in the indigeneity movement and large-scale migration, citizenship within national borders is challenged, and the borders in question are also contested. The book chronicles the discernible strains on the questions of indegeneity, citizenship, identity, and border making in the Northeast. The issues pertaining to indigeneity, citizenship, and state, are also a reminder of the residues of colonial doings that have had a colossal impact till this day. Through empirical evidence backed by theoretical underpinnings, each essay in the book demonstrates the diversity of approaches that can be used to interrogate the debate on indegeneity, citizenship, the state, and opens the conversation on Northeast India.
Contributed articles.
Keywords: Indigenous peoples -- India, Northeastern -- Ethnic identity; Ethnicity -- Political aspects -- India, Northeastern; India, Northeastern -- Political aspects -- Ethnic relations; India, Northeastern -- Politics and government; Citizenship -- India, Northeastern; SOCIAL SCIENCE / General